WATERSHED DAMAGE IN JAKARTA AREA (CASE STUDY ON CILIWUNG WATERSHED) - Dian Handayani; Al Asyary (UHAMKA Press, 2019)
The description of watershed damage and land degradation has shown an increase year by year. One of the watershed that has been degraded due to the change of land use is Ciliwung watershed. The purpose of this study is to identify the damaged watershed in DKI Jakarta area in 2015 (Ciliwung Watershed study case). The methodology used in this authorship is a study of literature on a wide range of scientific articles in the form of journals, books, and research related to the subject title. The main factor causing the damage to Watersheds (DAS) in Jakarta is the increase of development and infrastructure which caused the transition of land function which initially functioned as water storage area now turned into building, settlement and others. From the main factors, it can be concluded that the causes of watershed damage in DKI Jakarta area are lack of watershed management in DKI Jakarta, the absence of personnel in charge of watershed management, lack of community awareness and participation in efforts to preserve the watershed and less firm law enforcement.